Damage evolution and toughening mechanism in brick-and-mortar structure: Essential role of interface thickness ratio - Tian Qiu; Chengyu Guan; Lihong Liang (Polymer Testing)
The brick-and-mortar structure, known for its excellent mechanical properties, holds significant potential in biomimetic design. However, the effect of the interface on damage evolution and toughening mechanism remains unclear. This study employed 3D printing to fabricate brick-and-mortar structures with different interface thickness ratios and examined their mechanical properties and damage evolution through quasi-static tensile tests and digital image correlation (DIC) technology. The results indicate that increasing the interface thickness ratio reduces yield strength, fracture strength, and elastic modulus while increasing fracture strain. Higher interface thickness ratios also intensify interface damage, increase separation length, and cause the fracture mode of the brick-and-mortar structure to transition from hard phase fracture to pull-out fracture, significantly enhancing ductility. To elucidate the effect of interface thickness on elastic modulus, theoretical models based on tension-shear chain (TSC), shear-lag (SL), and strain gradient theory based on shear-lag (SGSL) models were applied and validated with experimental data. At higher thickness ratios, tensile deformation is dominated by the hard phase, necessitating a larger aspect ratio to counteract the low modulus of the interface. To achieve optimal mechanical performance, the study introduced an optimal aspect ratio and explored the synergistic optimization of interface thickness and the aspect ratio of the hard phase. The optimal aspect ratio can effectively compensate for the low modulus of the interface, thereby optimizing the balance between mechanical strength and toughness. These findings provide a reference and basis for future biomimetic material design.